Development and Validation of the Indonesian Version Self-Harm Inventory Using Rasch Model - Khadijah Lubis; Rani Mega Putri; Nur Wisma; Romi Fajar Tanjung; Sigit Dwi Sucipto (Department of Guidance and Counseling, FIP, Undiksha, 2026)
Self-harm among adolescents is currently a hot topic in various countries. This phenomenon has become a concern for counsellors and society in general. This study aims to develop an Indonesian version of the Self-Harm Inventory that can detect self-harm behaviour among high school students. The method used in this study is the ADDIE model, and the analysis was conducted using Rasch analysis. The pilot sample comprised 50 high school students, and the sample for estimating the prevalence of self-harm comprised 256 students selected by simple random sampling. The scale was developed in accordance with Indonesian culture. The results showed that the SHI scale had excellent validity and reliability based on item fit parameters, person-item reliability, and no item DIF was found in the inventory. The study also revealed the prevalence of self-harm among high school students identified using the SHI and showed that student self-harm behaviour was in the very low category. These findings are expected to form the basis for appropriate prevention and eradication interventions to build positive mental health and achieve psychological well-being among students.